Maternal perinatal representations and their associations with mother–infant interaction and attachment: A longitudinal comparison of Portuguese and Brazilian dyads. (8th March 2019) - Fuertes, Marina; Ribeiro, Camila; Gonçalves, Joana L.; Rodrigues, Cristina; Beeghly, Marjorie; Lopes‐dos‐Santos, Pedro; Lamônica, Dionísia A. C.
Abstract : Prior research in Western countries (mostly the US, Canada and northern Europe) indicates that mothers' representations are associated with mother–infant interaction quality and their child's attachment security later in the first year. Fewer studies, however, have evaluated whether these associations hold for mother–infant dyads in other countries, such as Brazil and Portugal. Although these countries share a similar language and culture, they differ on societal dimensions that may affect parenting attitudes and mother–infant relationships, such as economic stress, social organisation, social policy, and the availability of services for young families. In this longitudinal study, we followed two independent samples of Brazilian and Portuguese mother–infant dyads from the perinatal period to 12 months post‐partum. We assessed mothers' perinatal representations using semi‐structured interviews in the first 48 hours after the infant's birth, and evaluated the associations of these representations with mother interaction quality at 9 months and infant attachment at 12 months. Results were similar in each country, corroborating prior research in single Western countries: Mothers with more positive perinatal representations were more sensitive to their infants during free play at 9 months and were more likely to have infants classified as securely attached at 12 months.